2019
DOI: 10.4102/sajpsychiatry.v25i0.1342
|View full text |Cite
|
Sign up to set email alerts
|

Stress and coping mechanisms of officers of the South African Police Service based in Tzaneen, Limpopo province, South Africa

Abstract: BackgroundIn this study, stress is conceptualised as a psychological syndrome in response to stressors. Stress and inappropriate coping mechanisms constitute a serious problem in police profession. Organisational causes of stress, such as lack of support from management, are additional stressors. The ability to cope with this stress is influenced by marital status, gender, rank, age and years of service. In managing stress, police officers may use adaptive or maladaptive coping mechanisms.AimTo investigate str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
(41 reference statements)
0
2
0
7
Order By: Relevance
“…Similarly, a fewer studies reported that engaging in physical activities, entertainment sources like TV and music, thinking positively the problems can be solved and confront the problems, trying to find comfort in their religion, trying to see everything in a different light to make it more positive were the coping mechanisms likely to be adapted by them though their applicability in a crisis situation such as COVID-19 is questionable. [ 6 7 8 9 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a fewer studies reported that engaging in physical activities, entertainment sources like TV and music, thinking positively the problems can be solved and confront the problems, trying to find comfort in their religion, trying to see everything in a different light to make it more positive were the coping mechanisms likely to be adapted by them though their applicability in a crisis situation such as COVID-19 is questionable. [ 6 7 8 9 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ao observar na literatura sobre o estresse no ambiente policial, verifica-se estudos que associam fatores de riscos proveniente de 3 (três) fontes: aspectos individuaisque envolvem tipos de personalidade, resiliência e coping; os aspectos operacionaisque envolvem situações do trabalho na prática; os organizacionais, que estão ligados ao contexto institucional da policial 29,31 .…”
Section: Elementos Geradores De Estresse Entre Policiaisunclassified
“…Resultados análogos, também foram descritos em revisões sistemáticas que relacionaram estresse com o ambiente policial 41,44 . Além destes, outro fator muito associado e pouco estudado até o momento é sobre o impacto que o trabalho, desses agentes da segurança pública, geram nas relações familiares e as respectivas consequências 29,31,45,47 .…”
Section: Elementos Geradores De Estresse Entre Policiaisunclassified
See 2 more Smart Citations